2014
DOI: 10.1155/2014/985064
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Compact Microstrip Line-Based Balun-Bandpass Filter with High Common-Mode Suppression

Abstract: A new type of balun-bandpass filter was proposed based on the traditional coupled-line theory and folded open-loop ring resonators (OLRRs) configuration. For that, a new device with both filter-type and balun-type characteristics was investigated and fabricated. Both magnetic and electric coupling structures were implemented to provide high performance balun-bandpass responses. The fabricated balun-bandpass filters had a wide bandwidth more than 200 MHz and a low insertion loss less than 2.51 dB at a center fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…4 and 5). Magnetic coupling was easily achieved when each coupled resonator's side with maximum magnetic field was placed next to the other's [8,9]. The simulation results showed that the optimum coupling space between the microstrip lines and the OLRR resonators was 0.2 mm and between the two OLRR resonators was 0.61 mm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…4 and 5). Magnetic coupling was easily achieved when each coupled resonator's side with maximum magnetic field was placed next to the other's [8,9]. The simulation results showed that the optimum coupling space between the microstrip lines and the OLRR resonators was 0.2 mm and between the two OLRR resonators was 0.61 mm.…”
Section: Methodsmentioning
confidence: 99%
“…discriminative coupling [8,9]. The center valley of the OLRR resonators for the two different resonant frequencies had to be positioned at the proper location to obtain maximum magnetic coupling.…”
Section: Design Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, research on wideband high performance balun is meaningful for RF frond-ends. Over the past few years, much effort has been focused on this area [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%